FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI MASYARAKAT DALAM PROGRAM LAMPUNG MANGROVE CENTER (LMC) DI DESA MARGASARI KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR - Selvi Amelia; Indah Nurmayasari; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the level of community participation and factors related to the participation of the community in Lampung Mangrove Center (LMC) program in Margasari Village, Labuhan Maringgai, East Lampung Regency. The location was purposively chosen with the consideration that the activity of the center was in Margasari consisting of 12 hamlets. The research was conducted in June – August 2017. The results showed that the level of participation of most community members is included in a medium classification. Formal education level and cosmopolite characteristics relate significantly to their participation, while their age, the length of staying in the village, and their knowledge on the program do not relate to their participation.Key words: community, participation, program LMC